Pengaruh Kecerdasan Emosional dan Sikap Disiplin Terhadap Kinerja Guru di Madrasah Aliyah Negeri (MAN) Se-Kabupaten Pangandaran - Dadah Jubaedah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
So far, many people think that a high quality of a good job is influenced by a high quality of intellectual quotien (IQ). But in fact, the quality of Intelectual Quotien is not the main factor that influence on a Job of someone. There are other kind of intellectual called Emotional Quotien (EQ) and also a quality of good behaviour in working. The aim of this research is to know how high is the quality ofEmotional quotient, good behaviour and performance of the State Islamic Senior High School teachers’ in Pangandaran regency and also to know partially how high is the quality of the influence of Emotional Quotient and good behavior ofteacher simustaneously on their job performance. This research used qualitative and descriptive method. The sample of this research are 56 teacher of the State Islamic Senior High School in Pangandaran regency. To collect the dataThe researcher used a questioner that contain32 questions (9 questions for Emotional quotient variable, 8 question for Discipline performance variable, and 15 question for teacher performance and the interview to the vice school head of curriculum. To analyze the data, the researcher used analytical descriptive and the test of double linier regression method. This research shows that emotional quotient is in good quality (3,8 point);a good behavior of teachers is in very good quality (4.6 point); and teachers’ job performance is in Very Good Quality (4.4 point). Those mean that there are a significant influence between emotional quotient and good behaviour of the teacher on their job performance quality. In conclusion, emotional quotient and a good behaviorhas a great impact on the quality of teachers’ job performance. So, the teacher is obliged to increase their emotional quotient and quality of the job to develop their teaching performance without forgetting other factor that also influence to their performance quality.